PELAPORAN ARUS KAS PADA PT. KEDUNGMADU TROPICAL WOOD DI SAMARINDA - -, Lusiana - (EKONOMIA, 2017)
Cash flow statements describe or show the flow or movement of cash flows that is the acceptance of the sources and uses of cash in the period concerned in an enterprise and declared as one of the mandatory financial statements drawn up for the taking of decisions. The purpose of this research is to know the reporting of cash flow at PT. Kedungmadu Tropical Wood by 2013-2015.The problem in this research are PT. Kedungmadu Tropical Wood has been doing the preparation of cash flow statement in accordance with PSAK No. 2 and whether using direct method or indirect method is better for the company.The hypothesis of this research, namely PT KedungMadu Tropical Wood are not using direct method or indirect method in the preparation of the cash flow reporting and use of indirect methods better than direct methods.The research results show the PT. Kedungmadu Tropical Wood has not used the preparation of cash flow statement in accordance with PSAK No. 2.